As relações institucionais de poder envolvidas no processo penal - Ruiz, Fábio Nascimento (2018)
The main aim of this dissertation is to define power, seeking to explain the impact of this phenomenon both on the subjects that operate the law and on the institutions that apply it. In this regard, the classical philosophy and the juridical thinking that inspired it will be firstly analyzed, showing how mistaken interpretations disregard different nuances of power, such as the real concept of power. Thus, the juridical thinking - before discussing what power is and what its scope and impact are - begins to limit its exercise without knowing the extent of this phenomenon. The result is the production of a misdiagnosis, which has an impact on the epistemology of criminal procedural garantism. This research will analyze concepts of democracy and republicanism, as well as the idea of garantism and that of criminal procedural jurisdiction; in this analysis, it will be assessed how the desire for control of the exercise of power is unsuccessful, simply because the phenomenon was not properly inquired. Subsequently, the study will approach i) what we mean by power; ii) what constitutes subjects ontologically; iii) how the ontological constitution of the subject is related and shaped by the relations of power; iv) how the constituted subject is influenced by the institution which it belongs to, using, for that matter, the organic laws that discipline them ; (v) what is, in criminal procedural jurisdiction, the result of the application of the law as well as the fundamental guarantees of a person constituted and influenced by the application of the law and by the interpretation of other subjects that have a role in criminal procedure. Once the diagnosis of the lack of questioning of the 'power' phenomenon has been traced by classical juridical thinking, and the author's analysis of this phenomenon has been made, some partial solutions will be established for the imbalances in power relations